Molecular evolution across developmental time reveals rapid divergence in early embryogenesis. Issue 4 (1st August 2019) - Cutter, Asher D.; Garrett, Rose H.; Mark, Stephanie; Wang, Wei; Sun, Lei
Abstract: Ontogenetic development hinges on the changes in gene expression in time and space within an organism, suggesting that the demands of ontogenetic growth can impose or reveal predictable pattern in the molecular evolution of genes expressed dynamically across development. Here, we characterize coexpression modules of the Caenorhabditis elegans transcriptome, using a time series of 30 points from early embryo to adult. By capturing the functional form of expression profiles with quantitative metrics, we find fastest evolution in the distinctive set of genes with transcript abundance that declines through development from a peak in young embryos. These genes are highly enriched for oogenic function and transient early zygotic expression, are nonrandomly distributed in the genome, and correspond to a life stage especially prone to inviability in interspecies hybrids. These observations conflict with the "early conservation model" for the evolution of development, although expression-weighted sequence divergence analysis provides some support for the "hourglass model." Genes in coexpression modules that peak toward adulthood also evolve fast, being hyper-enriched for roles in spermatogenesis, implicating a history of sexual selection and relaxation of selection on sperm as key factors driving rapid change to ontogenetically distinguishable coexpression modules of genes. We propose that these predictable trends of molecular evolution for dynamically expressed genes across ontogeny predispose particular life stages, early embryogenesis in particular, to hybrid dysfunction in the speciation process.